Schaum's Statistics Supplementary Problem 12.30 : Chi-Squared Test for Goodness of Fit - Rader, David (McGraw-Hill's AccessEngineering, 2020)
This video demonstrates how to use the Chi-Squared test for goodness of fit, which determines how well sample data fits a theoretical distribution.